Bioprospecção de novos isolados e avaliação do potencial antimicrobiano, leishmanicida, antitumoral e perfil citotóxico dos cultivos puros e mistos de Paenibacillus polymyxa - Cavicchioli, Rafael (Universidade Federal de São Carlos, 2021)
Endophytes in general are among the most productive sources of secondary metabolites, presenting a series of biological activities and applications. It is estimated that approximately half of the antibiotics produced industrially, in addition to several other compounds, are produced by these organisms. According to the World Health Organization (WHO) 90% of bacterial strains are resistant to first-choice drugs. Therefore, the search for new molecules with antimicrobial activity is urgent. In view of this, the present study sought to optimize cultivation conditions for the production of fermented broth in order to achieve the greatest amount and diversity of secondary metabolites with biological action. Different types of cultures (axenic and mixed) were tested in order to evaluate their effectiveness in relation to: antimicrobial activity, leishmanicidal activity, antitumor activity and cytotoxicity. Based on the data obtained, a time of 168 hours was established for the production of broths. The mixed culture showed greater activity than the axenic culture in relation to antimicrobial activity, establishing 95.86% of inhibition at its lowest concentration tested for P. aeruginosa, 92.86% of inhibition against E.coli strains, 91.13% against Salmonella setubal. Using a concentration of 2500 µg, an inhibition of 82.5% was obtained in S. aureus and 86% in S. epidermidis. Regarding the leishmanicidal activity, the mixed culture broth showed a greater action than the simple culture when analyzed at lower concentrations. Cytotoxicity tests demonstrate that they are toxic only from a concentration of 10000 µg. From these results we can conclude that mixed cultures have great biological potential, in non-toxic concentrations. Multidrug resistance occurs in both Gram-positive and Gram-negative bacteria, which cause infections that cannot be treated with most conventional antibiotics. Due to these and other factors, microbial resistance is considered an alarming public health problem, showing an increasing number of infections caused by resistant bacteria, which cause infections in hospitals and communities. When some type of infection can no longer be treated by first-line antibiotics, usually more expensive drugs must be selected for treatment. The longer duration of the illness and treatment in question, often in the hospitals themselves, increases health care costs. A report citing the top threats to antibiotic resistance from the CDC in the United States (2019 Antibiotic Resistance Threats Report) includes the latest national estimates of deaths and infections that highlight the ongoing threat of antibiotic resistance. According to the report, more than 2.8 million antibiotic-resistant infections occur in the US each year, and more than 35,000 people die as a result. Based on these and other data, the second part of the study aims to find strains with antimicrobial activity from the plant species Coffea arabica and Xylopia aromatica and selects 6 strains that have great biotechnological potential. These strains were isolated in later studies and showed considerable antimicrobial activity.
Bioprospection of new isolates and evaluation of the antimicrobial, leishmanicidal, antitumor potential and cytotoxic profile of pure and mixed cultures of Paenibacillus polymyxa
Keywords: Endofíticos; Atividade biológica; Citotoxicidade; Endophytes; Biological activity; Cytotoxicity; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA::MICROBIOLOGIA INDUSTRIAL E DE FERMENTACAO